Chromium-coated cladding analysis under simulated LOCA burst conditions. (October 2022) - Sweet, Ryan; Mouche, Peter; Bell, Samuel; Kane, Kenneth; Capps, Nathan
Highlights: Demonstrated BISON's ability to appropriately model coated cladding tubes using a multilayered approach. Identify potential increases of the cladding margin to burst from the addition of the coating. Developed a method to assess the full cladding tube surface temperature distribution. Identified future work to identify margin to burst and data needs to develop a high temperature creep model. Abstract: Of the near-term accident-tolerant fuel concepts identified, chromium coatings have been shown to slow cladding oxidation without altering fuel system geometry or greatly affecting neutronic performance. To identify how coated cladding tubes perform under high-temperature accident conditions, pressurized-tube burst tests were conducted in the Severe Accident Test Station at Oak Ridge National Laboratory. To analyze how the coating affects cladding behavior, coated and uncoated cladding burst tests were simulated by using the BISON fuel performance code. Thermocouple data from these tests were fit into axial and azimuthal profiles and combined to generate 3D cladding surface temperatures, and pressure transducer data were compared until cladding failure. The cladding temperatures at failure and the internal gas pressure evolution show relatively good agreement between the simulation and experiment results. Simulations were then extrapolated to demonstrate the coatings effectiveness to increasing the cladding burst temperature by using a parametric evaluation of the initial tube gas pressure. This work demonstrates the possibility of an increased cladding failure margin under transient conditions due to the addition of chromium coating, and more pertinently, an increased cladding failure margin from more accurate experimental characterization.